WORK FROM HOME: POWER SUPPLY POLICY IN LANGKAI VILLAGE, CENTRAL KALIMANTAN - Tinus, Algavien; Ludang, Yetrie; Nawan (Acta Scientiae et Intellectus, 2024)
Currently, everyone is advised to keep their distance from each other and for workers to start working from home (WFH) which is a new thing for most people in Indonesia. It affects the use of electrical energy in connection with the use of electrical equipment in the household sector. Thus, the use of power plants with fossil energy sources will increasingly produce by-products such as air pollutant, which may affect the health of the environment and society, especially during this COVID-19 outbreak. To reduce dependence on fossil energy sources, it can be done by using new renewable energy sources such as environmentally friendly solar energy. One form is the use of rooftop solar power plants (Rooftop PLTS). The use of Rooftop PLTS also reduces greenhouse gas emissions, so that air pollution can be minimized. Thus, WFH can run according to health goals simultaneously, namely avoiding the impact of the pandemic and air pollution.